Kajian Teologis Tentang Konsep Keselamatan Karena Anugerah Menurut Roma 3:23-26 dan Relevansinya Terhadap Pemahaman Jemaat GKPPD Masa Kini. - Mestriyati Boangmanalu; Warseto F. Sihombing; Hanna Dewi Aritonang; Robert J.T Sitio; Reymond P. Sianturi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study focuses on the concept of salvation by grace as taught in Romans 3:23-26 and its relevance to the understanding of the GKPPD congregation today. Through a literature review with a theological approach, it was found that the doctrine of salvation by grace is the core of Christian teaching. In this passage, the Apostle Paul explains that all humans have sinned and fallen short of the glory of God (Romans 3:23). However, salvation is given through redemption in Christ Jesus, not as a result of human effort, but as a gift of God alone (Romans 3:24). Salvation is given through faith in the blood of Christ which redeems and takes away sin (Romans 3:25). In the context of the congregation today, the understanding of salvation by grace remains relevant. Many GKPPD congregations are still trapped in trying to obtain salvation through or obedience to the law, even though Romans 3:23-26 emphasizes the importance of faith in Christ's redemptive work. This study highlights that teaching about God's grace should foster a sense of gratitude, humility, and commitment to living in faith, not in fear or legalism. This study confirms that the concept of salvation through grace is the center of Christian faith teachings that need to continue to be lived and conveyed in the lives of the GKPPD congregation today and increase theological knowledge about the concept of salvation and can be a reference for theology students and reading materials in the IAKN Tarutung library.